2019
DOI: 10.1161/circresaha.119.314930
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Amplitude and Frequency Modulations Detect the Footprint of Rotational Activity and Reveal Stable Driver Regions as Targets for Persistent Atrial Fibrillation Ablation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…The prevalence of non‐PV triggers is variable among different studies, although they can be documented in up to 60% of patients with AF 71 . Moreover, extra PV trigger locations may also participate in AF maintenance as areas for driver sources sustaining the overall arrhythmia outside the PVs 72–74 …”
Section: Anatomically Based Approaches Beyond the Pulmonary Veinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of non‐PV triggers is variable among different studies, although they can be documented in up to 60% of patients with AF 71 . Moreover, extra PV trigger locations may also participate in AF maintenance as areas for driver sources sustaining the overall arrhythmia outside the PVs 72–74 …”
Section: Anatomically Based Approaches Beyond the Pulmonary Veinsmentioning
confidence: 99%
“…The CS is widely recognized as a focal source of AF triggers 56 . Moreover, the CS may also host AF drivers sustaining fibrillation dynamics 72 . This role as a critical driver for AF maintenance may be explained by the fact that the CS is surrounded by a myocardial sleeve whose fiber direction abruptly changes with respect to the contiguous left atrial wall 95 .…”
Section: Anatomically Based Approaches Beyond the Pulmonary Veinsmentioning
confidence: 99%
“…Several studies in goats, sheep and pigs show that artificially maintained AF leads to increasingly longer episodes of sustained arrhythmia [9,[179][180][181]. As an example of the potential of these induced AF animal models, we have recently described transcriptomic and proteomic changes during different stages of the disease in sheep and shown that most significant changes occurred at early stages of disease progression [12].…”
Section: Animal Models Of Afmentioning
confidence: 99%
“…In human hearts with an abnormal heart rhythm, atrial fibrillation, the wave of an electrical impulse through the atrial muscle becomes disorganized in its sequence of activation. There has been mounting evidence that rotors, an action potential (AP) wave front (WF) in the shape of spiral, spins around its central core, and may be a sustaining mechanism of fibrillatory activity (3)(4)(5). Nearest its central core of a rotor, the single action potential wave front may spin at a fairly constant frequency within a rotation plane that is often parallel to the atrial tissue surface (6).…”
Section: Introductionmentioning
confidence: 99%
“…If the WF propagated centrifugally away from its core, then one might assume that the greatest increase in frequency shift would be detected by electrodes directly in front along the path of the core's movement. New ablation strategies are currently being formulated to target ablation at atrial regions with the highest dominant frequency of WFs (5). Yet, when rotors breached a perimeter of narrow spaced electrodes, the maximal frequency shifts (both highest and lowest simultaneously) occur at either side of the core's movement (2), not directly in front or behind of its path.…”
Section: Introductionmentioning
confidence: 99%